DIAGNOSTIC IMAGINGThe place of indirect venography tests after pulmonary computed tomography angiography in the diagnosis of pulmonary thromboemboli - Karaoglu, Oguzhan; Tertemiz, Kemal Can; Yilmaz, Erkan; Akkoclu, Atila; Çullu, Neşat; Elibol, Funda Dinc (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Aim : To investigate the effectiveness of indirect computed tomography (CT) venography applied after pulmonary CT angiography to patients with suspected pulmonary embolism. Material and methods: The study comprised 80 patients at high/moderate risk of pulmonary embolism (PE) according to the clinical findings. Computed tomography venography (CTV) was performed 3-3.5 minutes after taking pulmonary CTA images. Color Doppler ultrasonography (CDUS) of the lower extremities was applied to all patients before pulmonary CTA or within 24 hours after CTA. Results : Pulmonary embolism was determined in a total of 19 patients (23%). Six patients had deep venous thrombosis on CTV examination even though the CDUS findings were normal. Accepting color Doppler ultrasonography findings as the gold standard, the sensitivity of CTV in determining deep vein thrombosis (DVT) was found to be 100%, specificity 91%, positive predictive value 60%, negative predictive value 100%, likelihood of giving a positive result 11.1, and likelihood of giving a negative result 0. There was a statistically significant good degree of correlation between the two methods (r = 0.741, p < 0.001). Conclusions: Computed tomography venography examination applied after pulmonary CTA is a fast imaging technique that has high diagnostic value and can be an alternative to CDUS, especially when CDUS is insufficient in application and evaluation.